The Influence of Work Supervision and Work Experience on Work Productivity at the Toti Mori Donggo Bolo Gas Station, Bima Regency - Trian Febrian; Jaenab; Ikbal Irawan (CV Edujavare Publishing, 2026)
The purpose of this study is to examine and analyze the significant effect of work supervision and work experience, both partially and simultaneously, on employee productivity at the Toti Mori Donggo Bolo gas station, Bima Regency. This study employed a quantitative approach with an associative research design to examine the influence of work supervision and work experience on employee productivity at the Toti Mori Donggo Bolo gas station, Bima Regency. Data were collected from 31 employees through questionnaires, observations, and literature studies, and were analyzed using multiple linear regression with the assistance of SPSS software. The analysis included validity and reliability tests, classical assumption tests, correlation analysis, coefficient of determination, as well as t-tests and F-tests to determine the partial and simultaneous effects of work supervision and work experience on employee productivity. This study shows that work supervision has a positive and significant effect on employee work productivity at the Toti Mori Donggo Bolo gas station, Bima Regency, while work experience has no significant effect partially on work productivity. The results of simultaneous testing prove that work supervision and work experience together have a significant effect on employee work productivity. The coefficient of determination value of 47.1% shows that work productivity can be explained by these two variables, while the other 52.9% is influenced by other factors outside the research.